Preliminary Finding: Survey on Eating Disorder and Nutritional Status among Young Athletes - Wong, Fadzel Chee Ping; Sinpong HH (MEDWIN PUBLISHERS, 2021)
Introduction: It is well documented that eating disorders will have a negative impact on health status and athletic performance. The risks of eating disorders among athletes are required to be detected early before it affects athlete’s health and exercise performance. To date, there is still scanty information on eating disorder and nutritional status among young athletes in Sabah. Objective: The objective of this study was to determine eating disorders and nutritional status among young athletes in Sabah. Methodology: A total of 55 young athletes who are active representatives of sports competitions were selected to participate in this study. Eating attitudes test questionnaires (EAT-26) was used to determine eating disorder risk. International physical activity questionnaire (IPAQ) and 3-days food diary were used to determine nutritional status and physical activity level. Statistical Package for the Social Sciences (SPSS) version 27.0 was used to analyse the collected data. Pair-t test was used to compare energy intake of subjects with the recommended nutrient intake for Malaysia (PAL2.0). The significant level is p<0.05. Results: This study found that aesthetic and weight category sports were the highest risk for eating disorder. Energy intake (kcal/day) in the aesthetic, weight category, endurance and ball games did not significantly meet the daily energy intake recommendations. Conclusion: As a conclusion, majority of the subjects did not practice balanced diet and meet the recommended nutrient intake (RNI) especially in the aesthetic and weight category sports. These current findings are useful to detect early eating disorder among young athletes before it become critical and affect athletes’ exercise performance and health status.